A CASE OF MALABSORPTION PRESENTING WITH OSTEOMALACIA, COAGULOPATHY AND DELAYED PUBERTY - Sy, Clarence Aaron (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 26-year-old Filipino female presented initially with hematochezia. At the age of 2, following blunt abdominal trauma, the patient underwent intestinal bypass surgery (gastrojejunostomy). Thereafter, she experienced recurrent abdominal pain and diarrhea, with poor weight gain and short stature. Later, she would report delayed puberty (breast budding at 16; menarche at 18). She also reported bone and joint pain coupled with facial and extremity paresthesias, with X-rays revealing signs of osteopenia. Development of hematochezia resulting in severe anemia, in association with recurring gastrointestinal symptoms, prompted admission. Workup revealed elevations inprothrombin time, which improved following Vitamin K administration. GI endoscopy revealed no structural lesions. Skeletal X-rays revealed generalized decreases in mineralization, with lateral views showing concaving fishmouth deformities in the L1 to L5 vertebral bodies. Vitamin D levels were found to be deficient; this improved only following large doses of daily Vitamin D3 administration. Hormonal studies revealed hypogonadotropic hypogonadotropism, likely stemming from malnutrition.